2023
DOI: 10.1002/ajb2.16123
|View full text |Cite
|
Sign up to set email alerts
|

Differences in individual flowering time change pollen limitation and seed set in three montane wildflowers

Abstract: Premise: Changes to flowering time caused by climate change could affects plant fecundity, but studies that compare the individual-level responses of phenologically distinct, co-occurring species are lacking. We assessed how variation in floral phenology affects the fecundity of individuals from three montane species with different seasonal flowering times, including in snowmelt acceleration treatments to increase variability in phenology. Methods: We collected floral phenology and seed set data for individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…However, we found that abundance increased steadily over our data collection period (Supplementary material Fig. S2), which indicates that pollinators may not be more limiting over time and is consistent with prior findings [72,73].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we found that abundance increased steadily over our data collection period (Supplementary material Fig. S2), which indicates that pollinators may not be more limiting over time and is consistent with prior findings [72,73].…”
Section: Discussionsupporting
confidence: 91%
“…Previous work has shown that pollen and pollinator limitation is often species-specific and/or context-dependent in RMBL plant communities [72,74,75], which suggests that the impact of co-flowering facilitation likely also depends on the context and individual species. Schiffer and colleagues (2023) found that early and middle-season species had higher fitness when they flowered separately from population peaks [72]. However, their late-season species, Potentilla pulcherrima , had the highest fitness when it flowered at its population peak.…”
Section: Discussionmentioning
confidence: 99%
“…Pollination limitation, in which plants produce more ovules than are ultimately fertilized, can limit seed production, reducing colonization opportunities and wasting reproductive effort [ 172 , 173 ]. Plant phenological shifts related to climate change (e.g., early or delayed flowering) may increase or decrease individual fecundity [ 174 , 175 ], suggesting strong variation in seed production could occur across a species’ geographic range, which could enhance or reduce the colonization ability of specific populations. For example, the fecundity in eastern North American forests was shown to be highest towards southern edges of species’ distributions, limiting northward spread, whereas the ample fecundity and higher recruitment in western forests is facilitating tree species’ migration to higher latitudes [ 19 ].…”
Section: Colonization Abilitymentioning
confidence: 99%